2019
DOI: 10.1039/c8fo01938j
|View full text |Cite
|
Sign up to set email alerts
|

Non-chemically modified waxy rice starch stabilised wow emulsions for salt reduction

Abstract: Water-in-oil-in-water emulsions containing an internalised salt solution were stabilised with non-chemically modified waxy rice starch (WRS), and octinyl succinic anhydride (OSA) as reference, to release salt during oral processing due to amylase-induced destabilisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
2
16
1
Order By: Relevance
“…In multiple emulsion droplets with numerous small internal droplets, some internal droplets were located very close to the external interface, which led to fast swelling of internal droplets and their burst from the oil phase. (W 1 /O)/W 2 emulsions containing 1 2 wt% PGPR and 1 4 wt% gelatinized waxy rice starch prepared by Kasprzak et al (2019) using a highshear mixer showed a high long-term stability, which means that stability of multiple emulsions during storage under stagnant conditions strongly depends on droplet size, probably due to different creaming rates.…”
Section: Encapsulation Efficiency and Storage Stability Of Emulsionsmentioning
confidence: 99%
“…In multiple emulsion droplets with numerous small internal droplets, some internal droplets were located very close to the external interface, which led to fast swelling of internal droplets and their burst from the oil phase. (W 1 /O)/W 2 emulsions containing 1 2 wt% PGPR and 1 4 wt% gelatinized waxy rice starch prepared by Kasprzak et al (2019) using a highshear mixer showed a high long-term stability, which means that stability of multiple emulsions during storage under stagnant conditions strongly depends on droplet size, probably due to different creaming rates.…”
Section: Encapsulation Efficiency and Storage Stability Of Emulsionsmentioning
confidence: 99%
“…The non-chemical modification of the waxy rice starch involved the gelatinisation of the starch ingredient via the frictional heat input during the secondary emulsification step using a high shear overhead mixer. This procedure was previously found to provide long-term stability to o/w emulsions (Kasprzak et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Compartmentalisation of salt in liquid foods is challenging due to the fact that salt is water soluble. However, one of us has previously demonstrated that this challenge can be overcome by encapsulating salt in the internal aqueous phase of a water-in-oil-in-water (w 1 /o/w 2 ) emulsion (Kasprzak et al, 2019). The internal aqueous phase (w 1 ), comprising a higher level of salt than the external aqueous phase (w 2 ), was emulsified into sunflower oil containing the lipophilic emulsifier polyglycerol polyricinoleate (PGPR).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations